Twin lexical collocations in legal late Middle English - Iglesias-Rábade, Luis (Adam Mickiewicz University, 2007)
The aim of this study is an attempt to examine the occurrence and expansion of lexical clusters (collocations) in legal late Middle English and to determine whether or not these multi-word items are recurrent, cohesive, arbitrary and domain-dependent lexical clusters. The definition and categorisation of collocations are analysed on the basis of the statistical probability of co-occurrence of some vocabulary items (textual perspective). For this purpose non-technical English texts of late Middle English were chosen that provided us with a common corpus that operated as a point of reference. Likewise a smaller body of legal texts of the same period was collected. The WordSmith program was used to create word lists of the two corpora and compute the key words of the legal corpus. This study concentrates on twin lexical collocations (e.g. geue & bequeath) found in the first 100 salient words of the legal corpus as it is assumed here that a significantly frequent lexical word in the legal corpus plays an important role in collocational patterns.